PSYCHOLOGICAL ASSISTANCE IN SOLVING INTIMATE-PERSONAL PROBLEMS OF YOUTH BY ART THERAPY (Pedagogy of Higher and Secondary Education, 2022)
In the article experience of the use of expressive methods of self-expression and art-therapy is analysed in-process with the intimately-personality problems of youths.
Keywords: art-terapy; ideals; frames